Penyesuaian Pengasuhan Orang Tua Terhadap Anak Putus Sekolah: Studi Masyarakat Di Desa Paseban Jember - Dewi Laksmita Wijayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember, 2025)
The phenomenon of school dropouts is still a significant problem in Paseban Village, Jember Regency. Although the government has launched a 12-year compulsory education program, its implementation has not been fully effective in Paseban. Low interest in learning, bullying, parental divorce, and limited educational facilities are triggers for children to drop out of school. This study aims to determine how parents adjust their care for school dropouts in Paseban Village. This study uses John W. Santrock's parenting theory and James Coleman's social capital theory to analyze the phenomenon. The approach used is qualitative with a phenomenological method. Data collection techniques include observation, in-depth interviews, and documentation, with the main informants being parents who have children who drop out of school and teachers as supporting informants. Data validity techniques are carried out by triangulating methods, sources, and theories. Data analysis through the process of data reduction, categorization, and thematic presentation. The results of the study showed that school dropouts were caused by internal factors such as lack of motivation, academic difficulties, low interest in learning. Then external factors that occur due to bullying, divorce, and lack of educational facilities. Parenting patterns have changed from authoritarian, democratic, to permissive, where parents tend to let children make their own decisions. Weak social capital such as trust in schools and community norms that do not support education also strengthen children's decisions not to return to school.
Reuploud file repositori 13 Apr 2026_Firli_tata
Keywords: parenting patterns; social capital; school dropouts